A copper(I) complex with two unpaired electrons, synthesised by oxidation of a copper(II) complex with two redox-active ligands - Werr, Marco; Kaifer, Elisabeth; Enders, Markus; Asyuda, Andika; Zharnikov, Michael; Himmel, Hans-Jörg (Angewandte Chemie. International edition, 2021)
Two homoleptic copper(II) complexes [Cu(L1)2] and [Cu(L2)2] with anionic redox-active ligands were synthesised, one with urea azine (L1) and the other with thio-urea azine (L2) ligands. One-electron oxidation of the complexes initiates an unprecedented redox-induced electron transfer process, leading to monocationic copper(I) complexes [Cu(L1)2]+ and [Cu(L2)2]+ with two oxidised ligands. While [Cu(L1)2]+ is best described as a CuI complex with two neutral radical ligands that couple antiferromagnetically, [Cu(L2)2]+ is a CuI complex with two clearly different ligand units in the solid state and with a magnetic susceptibility close to a diamagnetic compound. Further one-electron oxidation of the complex with L1 ligands results in a dication [Cu(L1)2]2+, best described as a CuI complex with a twofold oxidised, monocationic ligand and a neutral radical ligand. The stability in at least three redox states, the accumulation of spin density at the ligands and the facile ligand-metal electron transfer make these complexes highly attractive for a variety of applications; here the catalytic aerobic oxidation of alcohols to aldehydes is tested.